Gallid herpesvirus 3 SB-1 strain as a recombinant viral vector for poultry vaccination - Sadigh, Y; Powers, C; Spiro, S; Pedrera, M; Broadbent, A; Nair, V (Springer Nature, 2018)
Live herpesvirus-vectored vaccines are widely used in veterinary medicine to protect against many infectious diseases. In poultry, three strains of herpesvirus vaccines are used against Marek’s disease (MD). However, of these, only the herpesvirus of turkeys (HVT) has been successfully developed and used as a recombinant vaccine vector to induce protection against other avian viral diseases such as infectious bursal disease (IBD), Newcastle disease (ND) or avian influenza (AI). Although effective when administered individually, recombinant HVT vectors have limitations when combined in multivalent vaccines. Thus there is a need for developing additional viral vectors that could be combined with HVT in inducing protection against multiple avian diseases in multivalent vaccines. Gallid herpesvirus 3 (GaHV3) strain SB-1 is widely used by the poultry industry as bivalent vaccine in combination with HVT to exploit synergistic effects against MD. Here, we report the development and application of SB-1 as a vaccine vector to express the VP2 capsid antigen of IBD virus. A VP2 expression cassette was introduced into the SB-1 genome at three intergenic locations (UL3/UL4, UL10/UL11 and UL21/UL22) using recombineering methods on the full-length pSB-1 infectious clone of the virus. We show that the recombinant SB-1 vectors expressing VP2 induced neutralising antibody responses at levels comparable to that of commercial HVT-based VAXXITEKHVT+IBD vaccine. Birds vaccinated with the experimental recombinant SB-1 vaccine were protected against clinical disease after challenge with the very virulent UK661 IBDV isolate, demonstrating its value as an efficient viral vector for developing multivalent vaccines against avian diseases.